Bacterioplankton community resilience to ocean acidification: evidence from microbial network analysis. (20th November 2015) - Wang, Yu; Zhang, Rui; Zheng, Qiang; Deng, Ye; Van Nostrand, Joy D.; Zhou, Jizhong; Jiao, Nianzhi
Abstract: Ocean acidification (OA), caused by seawater CO2 uptake, has significant impacts on marine calcifying organisms and phototrophs. However, the response of bacterial communities, who play a crucial role in marine biogeochemical cycling, to OA is still not well understood. Previous studies have shown that the diversity and structure of microbial communities change undeterminably with elevated p CO2 . Here, novel phylogenetic molecular ecological networks (pMENs) were employed to investigate the interactions of native bacterial communities in response to OA in the Arctic Ocean through a mesocosm experiment. The pMENs results were in line with the null hypothesis that elevated p CO2 /pH does not affect biogeochemistry processes. The number of nodes within the pMENs and the connectivity of the bacterial communities were similar, despite increased p CO2 concentrations. Our results indicate that elevated p CO2 did not significantly affect microbial community structure and succession in the Arctic Ocean, suggesting bacterioplankton community resilience to elevated p CO2 . The competitive interactions among the native bacterioplankton, as well as the modular community structure, may contribute to this resilience. This pMENs-based investigation of the interactions among microbial community members at different p CO2 concentrations provides a new insight into our understanding of how OA affects the microbial community.